1999
DOI: 10.1002/(sici)1522-7189(199902)7:1<39::aid-nt38>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic lignans of Leucophyllum frutescens

Abstract: Bioassay-guided fractionation of the hexane:ethyl acetate (1:1) extract of the leaves of Leucophyllum frutescens (Berl.) I.M.Johnst (Scrophulariaceae) led to the isolation of its phytotoxic constituents diayangambin (1), epiyangambin (2), diasesartemin (3) and epiashantin (4). Phytotoxicity was demonstrated as inhibition of seed germination of Agrostis stolonifera cv. penncross (Poaceae) and inhibition of development of Lactuca sativa L. (Asteraceae) seedlings in a microassay using 24-well plates. Compound 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Our findings suggest that this species has antituberculosis activity against sensitive and resistant strains of Mycobacterium tuberculosis. Some phytotoxic lignans have been isolated from this plant (Rimando et al, 1999) and calmodulin inhibitors have been reported in the closely related species Leucophyllum ambiguum (Rojas et al, 2003). However, there are no previous reports on the antituberculosis activity and chemical nature of the antituberculosis compounds in Leucophyllum frutescens.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that this species has antituberculosis activity against sensitive and resistant strains of Mycobacterium tuberculosis. Some phytotoxic lignans have been isolated from this plant (Rimando et al, 1999) and calmodulin inhibitors have been reported in the closely related species Leucophyllum ambiguum (Rojas et al, 2003). However, there are no previous reports on the antituberculosis activity and chemical nature of the antituberculosis compounds in Leucophyllum frutescens.…”
Section: Resultsmentioning
confidence: 99%
“…Epiashantin, the most effective growth inhibitor in SW480 cells is found together with the related compounds yangambin and epiyangambin in medicinal plants with anti-mitotic activity (Rimando et al 1999) and was isolated from artemisia absinthum (wormwood), a spice used in liquors (Greger and Hofer 1980). The main activity of yangambin is inhibition of platelet activating factor (Castro-Faria-Neto et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Lignans are widely distributed in plants and derived from the phenylpropanoid pathway. These compounds exhibit interesting antimicrobic, antiviral, herbicidal, or antifeedant activities that are thought to participate in plant defence mechanisms against biotic stresses [11,12]. The cancer protective effects of dietary lignans have been also demonstrated [13] but not many data are available regarding the phytotoxic activity of this class of compounds or their ability to interact with other plant organisms.…”
Section: Introductionmentioning
confidence: 99%